1992
DOI: 10.4197/mar.3-1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Oxygen Consumption and Heart Rate in the Inter-Tidal Wedge Clam, Donaxfaba (Gmelin)

Abstract: The effect of temperature on the rate of oxygen consumption and heart rate has been investigated in the Red Sea, inter-tidal wedge clam Donax faba. The 010 values for both oxygen consumption and heart rate were often < 2.5 and were relatively constant over a wide range of temperature. This suggests that wedge clam is well adapted for life in high temperature environment. It was noted, however, that behavioural mechanisms were important in reducing the degree of temperature stress that could be experienced in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…However, in the present study, Donax faba nei ther exhibited tidal pattern nor a semilunar migratory pattern but rather a seasonal mi gratory pattern related to the seasonal variation in the mean sea level. Similar patterns of behavior were observed for semi-terrestrial crabs [6][7][8]10] .…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…However, in the present study, Donax faba nei ther exhibited tidal pattern nor a semilunar migratory pattern but rather a seasonal mi gratory pattern related to the seasonal variation in the mean sea level. Similar patterns of behavior were observed for semi-terrestrial crabs [6][7][8]10] .…”
Section: Introductionsupporting
confidence: 75%
“…There is a remarkable seasonal variation, in the mean sea level in the Red Sea due to the monsoon effect [5][6][7][8]12,13,38] . Patzert [12] suggested that the monsoon wind reversal is the major factor controlling sea level.…”
Section: Mean Sea Levelmentioning
confidence: 99%
See 3 more Smart Citations